Electrical and Optical Properties of Indium Zinc Oxide (IZO) Thin Films by Continuous Composition Spread - Lee, J. J.; Kim, J. S.; Yoon, S. J.; Cho, Y. S.; Choi, J. W. (AMER SCIENTIFIC PUBLISHERS, 2013)
Indium zinc oxide (IZO) films were deposited on glass substrate at room temperature using off-axis RE sputtering-continuous composition spread (CCS) system. The full range composition of IZO films were controlled by the deposition rate and thickness profiles of In2O3 and ZnO target. The structural, electrical and optical properties of IZO thin films were measured as functions of position. IZO thin film had the lowest resistivity and highest carrier concentration at the position of 15 mm (5.02 x 10(-4) Omega cm, 3.9 x 10(20)/cm(3)). And IZO thin film had high transmittance in visible region at measured all positions. This study has investigated to explore the new composition of IZO films using CCS system.